Examining Farmer and Seed Construction in the Context of Seed Policy: A Social Constructionist Perspective - Wulandari, Catur; Amaliyah, Anita (Faculty of Social Science, Universitas Negeri Padang, 2024)
The role of crop seeds extends beyond the essential task of achieving food security and is embedded in technical, social, economic, and political debates. The character of seeds and their association with farmers has transformed, influenced by social constructs embedded within policies. This research endeavors to scrutinize the impact of the social construction of farmers and seeds within national policies on their respective roles at the grassroots level. The foundational premise of this approach posits that the social construction of the target demographic significantly shapes the perspectives of public officials, thereby influencing agendas and policy formulations. Employing a qualitative methodology, this study entails the analysis of both secondary data, encompassing national seed policies, and primary data acquired through the Seed Self-Reliant Village initiative in Ngasin Village. The findings elucidate a negative construction of smallholder farmers, depicting them as lacking influence, while seeds are portrayed as integral production materials geared towards augmenting productivity. At the local level, knowledge pertaining to seeds is cultivated based on productivity criteria, delineating the appropriateness of seeds for dissemination. This research contributes valuable insights to the realm of public policy analysis, underscoring the infrequently utilized yet potent social construction approach.